Analisis Waktu Tempuh Kendaraan Bermotor Dengan Metode Estimasi Instantaneous Model (Studi Kasus: Jalan Pekanbaru - Bangkinang Km.19 Sampai Dengan Km. 25) - Rijalul Haqqi; Horas. SM Marpaung; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Travel time information is one of reference to planning a trip. Therefore it is needed a reliable travel time estimation method. Travel time estimation models used namely Instantaneous model using time mean speed (TMS) and space mean speed (SMS) based on spot speed data. Reability test result for instantaneous model based on TMS get time travel for Research road segment get value 7,472 minutes and based on SMS get value 7,785 minutes. Therefore the application of instantaneous estimation method of the model on the research road can be used to predict the travel time of the vehicleKeywords: Travel time estimation, Instantaneous Models, Spot speed